The Waldorf Pedagogy contributions for the learning process and the neurologic development of children in elementary school (Research, Society and Development, 2018)
This study aims to reflect on the pedagogical practices of Waldorf Pedagogy. The objective of this study was to analyze the contributions of this methodology to the learning process related to child neurologic development. A bibliographical research was carried out considering the contribution of several authors, trying to emphasize the importance of creating a favorable environment to promote the child's development, influencing the teaching-learning process. It was concluded that the Waldorf Pedagogy contributes meaningfully to children's learning and development, influencing the main processes for the acquisition of knowledge.